Analisis Percepatan Pembangunan Gedung Asrama Mahasiswa Nusantara Manado dengan Penerapan Building Information Modelling (BIM) - Kalumata, Fardi; Hosang, Mercy (Jurnal Informasi, Sains dan Teknologi, 2025)
The construction of the Manado Student Dormitory (AMN) is one of the President's priorities, the construction of which is based on PP No. 106 of 2021. The aim of building the AMN is so that students from various regions studying in North Sulawesi can interact with each other and get to know and respect each other's cultures. After the pre-construction meeting (PCM) was carried out, the service user instructed that acceleration be made by shortening the implementation time. To implement these instructions, PT. Widya Satria implemented the BIM (building information modelling) system to accelerate the work, by modelling the construction phase starting from BIM 3D (modelling), BIM 4D (scheduling), and BIM 5D (quantity take off). Accelerating work is carried out by applying the fast track method so that any work that has a long critical path time can be shortened by overlapping work between one stage and another that can be done together. The implementation results simulate that the work can be completed faster than the contract time with a workforce requirement of 296 people, 1 (one) tower crane unit, and 1 (one) mobile crane work unit, even after implementing BIM in the construction of AMN Manado, all stakeholders It is easy for the holder to coordinate and control work progress.